The Aggregation and Translocation of Nanosilica Lunar Dust in the Pulmonary Surfactant Monolayer - Tang, Kailiang (Langmuir : the ACS journal of surfaces and colloids, 2025)
Nanosilica lunar dust (NSLD) particles pose significant respiratory hazards to astronauts, with their aggregation in the pulmonary surfactant (PS) monolayer exacerbating pulmonary nanotoxicity. However, the underlying aggregation mechanisms and translocation characteristics of NSLDs in the PS monolayer remain unclear. Here, by performing coarse-grained molecular dynamics simulations, we investigate them and consider different sizes (3 and 6 nm), shapes (sphere, ellipsoid, and cube), and morphological complexity (with and without bulges). The key findings are as follows: (1) the movement patterns of spherical and ellipsoidal NSLDs contrast with those of cubic NSLDs. Consequently, the translocation time, embedding depth, aggregation state, and penetration characteristics of aggregates composed of spherical and ellipsoidal NSLDs exhibit opposite trends to those of aggregates composed of cubic NSLDs. (2) The impact of aggregates composed of spherical and ellipsoidal NSLDs on the Sz value also contrasts with that of aggregates composed of cubic NSLDs. For PS monolayer area, aggregates containing one or two shapes of NSLDs show a decreasing trend with the number of 6 nm NSLDs increases. In contrast, when the aggregates include three different shapes of NSLDs, this trend is reversed. (3) As the number of bulges increases, the aggregation and translocation characteristics of NSLDs in the PS monolayer become more complex, exhibiting different trends depending on the specific situation. In general, the aggregation and translocation characteristics of aggregates composed of spherical and ellipsoidal NSLDs contrast with those of aggregates composed of cubic NSLDs, and the presence of bulges adds complexity to the overall behavior of these aggregates